Aluminum current collector, method for manufacturing the same, and secondary battery and electric device
Patent Information
- Application Number
- CN202511185884.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-08-22
AI Technical Summary
[0003]传统方法多采用直流电化学腐蚀或化学刻蚀工艺提升表面粗糙度,但存在以下问题:采用直流腐蚀法,表面孔洞分布不均,力学性能易劣化;化学刻蚀工艺粗糙度提升有限,比接触电阻降低不显著;复合涂层法增加工艺复杂度,能耗高,良品率低,成本较高
[0005]本申请旨在至少在一定程度上解决现有技术中存在的技术问题。为此,本申请提出了铝集流体及其制备方法、二次电池和用电设备,利用本申请的制备方法能够在铝箔表面形成均匀微米级蜂窝状结构,提升铝箔表面粗糙度,降低比接触电阻,所得铝集流体兼具高力学性能和低比接触电阻。并且,本申请简化了工艺流程,缩短处理时间,降低能耗,提升效率,适于规模化生产应用。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of materials. Specifically, this application relates to aluminum current collectors and their preparation methods, as well as secondary batteries and electrical devices. Background Technology
[0002] As a key component of rechargeable batteries, the surface properties of aluminum current collectors directly affect battery performance. In terms of mechanical properties, aluminum foil must possess excellent tensile strength to withstand the mechanical stresses during electrode coating, rolling, and cell winding / stacking. Insufficient mechanical properties can lead to current collector breakage, wrinkling, or localized deformation, subsequently causing active material shedding, lithium dendrite growth, and even internal short circuits, seriously threatening battery safety and cycle life. At the electrical performance level, the specific contact resistance between the aluminum current collector and the cathode material is a core factor affecting the battery's internal resistance. Increased specific contact resistance significantly reduces energy conversion efficiency, leading to ohmic heat accumulation during charging and discharging, exacerbating capacity decay, and triggering the risk of thermal runaway. Therefore, aluminum current collectors with both high mechanical stability and low contact resistance are crucial foundational materials for achieving high energy density, long cycle life, and high safety in power batteries.
[0003] Traditional methods often employ direct current electrochemical etching or chemical etching processes to improve surface roughness, but these methods have the following problems: When using direct current etching, the surface pores are unevenly distributed, and the mechanical properties are easily degraded; the roughness improvement of chemical etching is limited, and the reduction in contact resistance is not significant; composite coating methods increase process complexity, have high energy consumption, low yield, and high cost.
[0004] Therefore, there is an urgent need to develop novel aluminum current collector preparation technologies that balance structural stability and electrochemical interface optimization. Summary of the Invention
[0005] This application aims to at least partially address the technical problems existing in the prior art. To this end, this application proposes an aluminum current collector and its preparation method, a secondary battery, and an electrical device. The preparation method of this application can form a uniform micron-scale honeycomb structure on the surface of aluminum foil, improving the surface roughness of the aluminum foil and reducing the specific contact resistance. The resulting aluminum current collector possesses both high mechanical properties and low specific contact resistance. Furthermore, this application simplifies the process flow, shortens processing time, reduces energy consumption, and improves efficiency, making it suitable for large-scale production applications.
[0006] In one aspect of this application, a method for preparing an aluminum current collector is provided. According to an embodiment of this application, the method includes: pretreating an aluminum foil to remove an oxide layer and contaminants from the surface of the aluminum foil; placing the pretreated aluminum foil in an electrolyte for AC etching treatment to obtain an etched aluminum foil; and post-treating the etched aluminum foil to obtain the aluminum current collector; wherein the AC etching treatment uses asymmetric AC current.
[0007] According to the preparation method of this application embodiment, asymmetric alternating current is used, and a high forward current (10-30 mA / cm²) is applied. 2 This promotes the anodic dissolution of aluminum foil, forming micron-sized pores; reverse low current (5-10 mA / cm) 2 This process inhibits excessive corrosion, triggers local redeposition, optimizes pore wall structure, ensures that reverse repair time is greater than forward corrosion time, and forms a low aspect ratio structure. This results in a uniform micron-scale honeycomb structure on the aluminum foil surface, which not only reduces the interfacial gap between the aluminum foil and the cathode material, increases the specific surface area and effective contact area, improves roughness, and reduces specific contact resistance, but also inhibits hydrogen evolution reaction, reduces the mechanical damage of bubbles to the pore walls, strengthens structural stability, and thus improves the mechanical properties of the aluminum foil.
[0008] According to embodiments of this application, the method for preparing the aluminum current collector may further include the following additional technical features: According to an embodiment of this application, the frequency of the asymmetric alternating current is 10 Hz to 200 Hz.
[0009] According to an embodiment of this application, the duty cycle of the asymmetric alternating current is 1:2 to 1:4.
[0010] According to an embodiment of this application, the forward current density of the asymmetric alternating current is 10 mA / cm². 2 ~30 mA / cm 2 .
[0011] According to an embodiment of this application, the reverse current density of the asymmetric alternating current is 5 mA / cm². 2 ~10 mA / cm 2 .
[0012] According to an embodiment of this application, the temperature of the alternating current etching treatment is 20°C to 60°C.
[0013] According to an embodiment of this application, the time for the alternating current etching treatment is 10 s to 180 s.
[0014] According to embodiments of this application, the electrolyte includes hydrochloric acid, sulfuric acid, and nitric acid.
[0015] According to an embodiment of this application, the electrolyte is obtained by mixing concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid with deionized water in a volume ratio of (1~5):(1~3):(1~3); wherein the volume of the deionized water is less than or equal to the sum of the volumes of the concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid.
[0016] According to an embodiment of this application, the pretreatment includes: cleaning the aluminum foil with an alkaline solution.
[0017] According to an embodiment of this application, the alkaline solution comprises a sodium hydroxide solution, wherein the sodium hydroxide solution contains 2 to 8 wt% sodium hydroxide by mass.
[0018] According to an embodiment of this application, the temperature of the alkaline cleaning solution is 30℃~50℃, and the time is 10 s~30 s.
[0019] According to an embodiment of this application, the post-processing includes washing with water and drying.
[0020] According to an embodiment of this application, the drying temperature is 50°C to 70°C.
[0021] In another aspect of this application, an aluminum current collector is provided. According to an embodiment of this application, the aluminum current collector is prepared by the aforementioned method for preparing aluminum current collectors.
[0022] According to an embodiment of this application, the surface of the aluminum current collector has a honeycomb structure.
[0023] According to an embodiment of this application, the surface roughness Ra of the aluminum current collector is not less than 1.5 μm.
[0024] According to an embodiment of this application, the specific contact resistance of the aluminum current collector is 15 mΩ·cm. 2 ~20 mΩ·cm 2 .
[0025] According to an embodiment of this application, the tensile strength retention rate of the aluminum current collector is not less than 95%.
[0026] In another aspect of this application, a secondary battery is proposed. According to an embodiment of this application, the secondary battery includes the aforementioned aluminum current collector.
[0027] In another aspect of this application, an electrical device is proposed. According to an embodiment of this application, the electrical device includes the aforementioned secondary battery.
[0028] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0029] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0030] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.
[0031] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0032] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this application but do not exclude other contents.
[0033] This application discloses aluminum current collectors and their preparation methods, as well as secondary batteries and electrical devices, which will be described in detail below.
[0034] Preparation method of aluminum current collector In one aspect of this application, a method for preparing an aluminum current collector is provided. According to an embodiment of this application, the method includes: pretreating an aluminum foil to remove an oxide layer and contaminants from the surface of the aluminum foil; placing the pretreated aluminum foil in an electrolyte for AC etching treatment to obtain an etched aluminum foil; and post-treating the etched aluminum foil to obtain the aluminum current collector; wherein the AC etching treatment uses asymmetric AC current.
[0035] In this paper, the term "asymmetric alternating current" refers to alternating current with different forward and reverse current densities.
[0036] In this paper, the term "forward" refers to the direction of high current, and the term "reverse" refers to the direction of low current.
[0037] The preparation method of this application uses asymmetric alternating current, passing through a high forward current (10-30 mA / cm). 2 This promotes the anodic dissolution of aluminum foil, forming micron-sized pores; reverse low current (5-10 mA / cm) 2This process inhibits excessive corrosion, triggers local redeposition, optimizes pore wall structure, ensures that the reverse repair time is greater than the forward corrosion time, and forms a low aspect ratio structure. This results in a uniform micron-scale honeycomb structure on the aluminum foil surface, which not only reduces the interfacial gap between the aluminum foil and the cathode material, increases the specific surface area and effective contact area, improves roughness, and reduces specific contact resistance, but also inhibits hydrogen evolution reaction, reduces the mechanical damage of bubbles to the pore walls, strengthens structural stability, and thus improves the mechanical properties of the aluminum foil. However, if symmetrical alternating current is used for alternating current corrosion treatment, it will result in insufficient pore wall repair, excessively high reverse current, hydrogen evolution reaction tearing the pore walls, stress concentration, and decreased mechanical properties.
[0038] According to embodiments of this application, the frequency of the asymmetric alternating current is 10 Hz to 200 Hz. In some embodiments, the frequency of the asymmetric alternating current is 10 Hz, 20 Hz, 40 Hz, 50 Hz, 60 Hz, 80 Hz, 100 Hz, 120 Hz, 140 Hz, 150 Hz, 160 Hz, 180 Hz, or 200 Hz. This allows for a denser and more uniform micron-scale honeycomb structure, further improving roughness, reducing specific contact resistance, and shortening the processing time.
[0039] According to embodiments of this application, the duty cycle of the asymmetric alternating current is 1:2 to 1:4. In some embodiments, the duty cycle of the asymmetric alternating current is 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.5, 1:3.6, 1:3.8, or 1:4.
[0040] In this paper, the term "duty cycle of asymmetric alternating current" refers to the time ratio of forward current to reverse current within a complete current cycle. By employing the aforementioned duty cycle and a timing design of "short-term strong corrosion - long-term weak repair," the amount of redeposition on the pore wall was increased, the tensile strength retention rate was ≥95%, and the mechanical properties were enhanced. Simultaneously, the uniformity of pore distribution was improved by 40% (compared to DC corrosion), and the effective current utilization rate was improved.
[0041] According to an embodiment of this application, the forward current density of the asymmetric alternating current is 10 mA / cm². 2 ~30 mA / cm 2 The reverse current density is 5 mA / cm². 2 ~10 mA / cm 2 In some embodiments, the forward current density of the asymmetric alternating current is 10 mA / cm². 2 15 mA / cm 2 20 mA / cm 2 25 mA / cm 230 mA / cm 2 The reverse current density is 5 mA / cm². 2 6 mA / cm 2 7 mA / cm 2 8 mA / cm 2 9 mA / cm 2 10 mA / cm 2 Meeting the above conditions for forward and reverse current densities is beneficial for forming a uniform and dense micron-scale honeycomb structure, further improving roughness, reducing specific contact resistance, and enhancing mechanical properties.
[0042] According to embodiments of this application, the temperature for AC etching is 20°C to 60°C. In some embodiments, the AC etching temperature is 20°C, 30°C, 40°C, 50°C, or 60°C, and the temperature variation during the AC etching process does not exceed 2°C. Controlling the electrolyte temperature to meet the above conditions during AC etching optimizes the ion diffusion rate and reaction activation energy, enabling controllable growth of the honeycomb structure and preventing localized overheating that could lead to grain boundary embrittlement, thus maintaining the ductility and tensile strength of the aluminum foil substrate. If the temperature fluctuation during AC etching exceeds 2°C, it will significantly affect the pit growth rate and the number of pores, directly impacting the performance of the etched foil product. Therefore, temperature fluctuations during etched foil production must be controlled within a small range.
[0043] According to embodiments of this application, the AC etching treatment time is 10 s to 180 s. In some embodiments, the AC etching treatment time is 10 s, 30 s, 60 s, 90 s, 120 s, 150 s, or 180 s. Therefore, the surface etching degree of the aluminum foil is suitable, forming a uniform micron-scale honeycomb structure, improving roughness, reducing specific contact resistance, and enhancing mechanical properties.
[0044] According to embodiments of this application, the electrolyte includes hydrochloric acid, sulfuric acid, and nitric acid. Hydrochloric acid, as a strong acid, provides a high concentration of Cl⁻, preferentially dissolving the aluminum matrix and destroying the oxide layer, thus initiating localized corrosion activity. Sulfuric acid has high conductivity and high viscosity, which improves the ion migration efficiency of the electrolyte to ensure uniform current distribution. At the same time, its adsorbed sulfate ions can form a dynamic barrier layer on the aluminum surface, slowing down the corrosion rate. The strong oxidizing properties of nitric acid promote the formation of a nanoscale passivation film on the aluminum surface. This film selectively dissolves during the reverse cycle of alternating current, forming a periodic "activation-passivation" cycle.
[0045] According to an embodiment of this application, the electrolyte is obtained by mixing concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid with deionized water in a volume ratio of (1~5):(1~3):(1~3); wherein the volume of the deionized water is less than or equal to the sum of the volumes of concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid. In some embodiments, the electrolyte is obtained by mixing concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid with deionized water in volume ratios of 1:1:1, 2:1:1, 3:1:1, 4:1:1, 5:1:1, 1:2:1, 2:2:1, 3:2:1, 4:2:1, 5:2:1, 1:3:1, 2:3:1, 3:3:1, 4:3:1, 5:3:1, 1:1:2, 2:1:2, 3:1:2, 4:1:2, 5:1:2, 1:1:3, 2:1:3, 3:1:3, 4:1:3, and 5:1:3 (the volume of the deionized water is the sum of the volumes of concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid). By controlling the H⁺ concentration gradient, the passivation film growth rate, and the solution viscosity within the above-mentioned volume ratios of concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid, a balance between corrosion depth and lateral expansion is achieved. The synergistic effect of this hydrochloric acid-sulfuric acid-nitric acid tribasic acid complex system enables controlled tunneling corrosion of aluminum foil under asymmetric alternating current, while keeping the tensile strength loss within 5%. This results in the formation of a uniform micron-scale honeycomb structure, improving roughness, reducing specific contact resistance, enhancing mechanical properties, and preventing excessive corrosion that leads to excessively deep and uneven pores, thus failing to effectively reduce specific contact resistance.
[0046] The corrosion depth increases exponentially with time, with 80% of the pores forming within the first 60 seconds. Controlling the processing time to within 10-180 seconds precisely limits the pore depth to 1-3 μm, preventing structural collapse caused by later lateral pore expansion. The hydrochloric acid-sulfuric acid-nitric acid tribasic acid composite system, through a rapid "activation-passivation" cycle (accelerated by asymmetric alternating current), shortens the processing time compared to traditional processes while maintaining uniformity.
[0047] Compared to the hydrochloric acid-sulfuric acid-nitric acid tricarboxylic acid complex system, the core advantage of the hydrochloric acid-sulfuric acid-dicarboxylic acid complex system lies in the strong oxidizing property of nitric acid, which can induce periodic passivation on the aluminum surface, forming a dynamic "activation-passivation" synergistic mechanism. Nitric acid generates a nano-scale Al₂O₃·xH₂O passivation film on the aluminum surface through an oxidation reaction. This film is selectively dissolved during the reverse cycle of alternating current, forming a uniform corrosion initiation point and inhibiting localized over-corrosion. Meanwhile, the Cl⁻ in hydrochloric acid preferentially attacks weak areas of the passivation film, while the SO₄²⁻ in sulfuric acid... 2-The lateral expansion of corrosion is regulated by adsorption. The synergistic effect of the three factors achieves a dynamic balance between corrosion depth and lateral expansion rate, which can form honeycomb-like pores (hydrochloric acid dominates longitudinal corrosion), and limit excessive thinning of pore walls through nitric acid passivation film (tensile strength retention rate ≥95%). At the same time, the high conductivity of sulfuric acid ensures uniform current density distribution, avoiding the aggravated intergranular corrosion caused by the lack of oxidizing components in traditional dicarboxylic acid complex systems.
[0048] According to embodiments of this application, the concentrated hydrochloric acid has a mass fraction of ≥36%; the concentrated sulfuric acid has a mass fraction of ≥98%; and the concentrated nitric acid has a mass fraction of ≥69%.
[0049] According to an embodiment of this application, the electrolyte is obtained by mixing concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid with deionized water in any manner.
[0050] According to embodiments of this application, the pretreatment includes cleaning the aluminum foil with an alkaline solution. This facilitates the thorough and rapid removal of the oxide layer and contaminants, such as oil, from the aluminum foil surface, preventing their residue from affecting the subsequent AC etching effect.
[0051] According to embodiments of this application, the alkaline solution comprises a sodium hydroxide solution, wherein the sodium hydroxide solution contains 2-8 wt% sodium hydroxide by mass, the alkaline cleaning temperature is 30°C-50°C, and the cleaning time is 10-30 seconds. This ensures thorough and rapid removal of the oxide layer and contaminants from the aluminum foil surface, while avoiding excessive reduction in aluminum foil thickness or even perforation due to high temperature or prolonged alkaline cleaning, thus reducing mechanical strength. In some embodiments, the sodium hydroxide solution may contain 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, etc.; the alkaline cleaning temperature may be 30°C, 35°C, 40°C, 45°C, 50°C, etc.; and the alkaline cleaning time may be 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds, etc.
[0052] According to embodiments of this application, the post-processing includes washing and drying. This removes electrolyte and residue, preventing their residue from affecting the quality of the aluminum foil. In some embodiments, the drying temperature is 50°C to 70°C. This allows for rapid drying and reduces damage to the aluminum foil.
[0053] Aluminum current collectors, secondary batteries and electrical equipment In another aspect of this application, an aluminum current collector is proposed. According to an embodiment of this application, the aluminum current collector is prepared by the aforementioned method for preparing aluminum current collectors. Thus, the aluminum current collector obtained using the method of this application has a uniform micron-scale honeycomb structure, improving the surface roughness of the aluminum foil and reducing the specific contact resistance, thereby enabling the aluminum current collector to possess both high mechanical properties and low specific contact resistance.
[0054] According to embodiments of this application, the surface roughness Ra of the aluminum current collector is not less than 1.5 μm. In some embodiments, the surface roughness Ra of the aluminum current collector is 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, or 3.0 μm. The surface roughness of the aluminum current collector can be measured according to ISO 4287 standard using a white light interferometer (Bruker ContourGT).
[0055] According to an embodiment of this application, the specific contact resistance of the aluminum current collector is 15 mΩ·cm. 2 ~20 mΩ·cm 2 In some embodiments, the specific contact resistance of the aluminum current collector is 15 mΩ·cm. 2 16 mΩ·cm 2 17 mΩ·cm 2 18 mΩ·cm 2 19 mΩ·cm 2 20 mΩ·cm 2 The specific contact resistance of aluminum current collectors can be tested using the four-probe method (Keithley 2450) at a constant current of 1 A.
[0056] According to embodiments of this application, the tensile strength retention rate of the aluminum current collector is not less than 95%. In some embodiments, the tensile strength retention rate of the aluminum current collector is 95%, 96%, 97%, 98%, or 99%. The tensile strength retention rate of the aluminum current collector can be tested according to the ASTM E8 standard at a tensile rate of 2 mm / min.
[0057] In another aspect, this application proposes a secondary battery. According to an embodiment of this application, the secondary battery includes the aforementioned aluminum current collector. Therefore, the secondary battery of this application exhibits excellent electrochemical performance.
[0058] According to embodiments of this application, the secondary battery includes a positive electrode sheet, which comprises the aforementioned aluminum current collector and a positive electrode active material disposed on at least one side of the aluminum current collector. The secondary battery can be a lithium-ion battery, a sodium-ion battery, or the like.
[0059] In another aspect, this application proposes an electrical device. According to an embodiment of this application, the electrical device includes the aforementioned secondary battery. Therefore, the electrical device of this application possesses excellent electrochemical performance.
[0060] Electrical devices may include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0061] It should be noted that the features and advantages described above regarding the preparation method of aluminum current collectors also apply to the aluminum current collector, secondary battery, and electrical equipment, and will not be repeated here.
[0062] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0063] Example 1 In this embodiment, the aluminum current collector is prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0064] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0065] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 100 Hz, a duty cycle of 1:3, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 40±2℃ and the time was 120 s.
[0066] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0067] Example 2 In this embodiment, the aluminum current collector is prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0068] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0069] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 180 Hz, a duty cycle of 1:4, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 50±2℃ and the time was 90 s.
[0070] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0071] Example 3 In this embodiment, the aluminum current collector is prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0072] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0073] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 80 Hz, a duty cycle of 1:2, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 30±2℃ and the time was 150 s.
[0074] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0075] Example 4 In this embodiment, the aluminum current collector is prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0076] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid and deionized water is 3:1:6.
[0077] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 100 Hz, a duty cycle of 1:3, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 40±2℃ and the time was 120 s.
[0078] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0079] Example 5 In this embodiment, the aluminum current collector is prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0080] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 45:3:20:32.
[0081] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 100 Hz, a duty cycle of 1:3, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 40±2℃ and the time was 120 s.
[0082] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0083] Comparative Example 1 In this comparative example, aluminum current collectors were prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0084] 2. DC corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0085] (2) Place the pretreated aluminum foil in the electrolyte and start the DC current with a current density of 20 mA / cm². 2 The temperature was 40±2℃ and the time was 120 s.
[0086] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0087] Comparative Example 2 In this comparative example, aluminum current collectors were prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0088] 2. Chemical etching: (1) Preparation of chemical etching solution: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated phosphoric acid (mass fraction 85%) and deionized water to obtain chemical etching solution. The volume ratio of concentrated hydrochloric acid, concentrated phosphoric acid and deionized water is 9:2:9.
[0089] (2) Place the pretreated aluminum foil in a chemical etching solution and process it at room temperature for 240s.
[0090] 3. Post-processing: The etched aluminum foil was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0091] Comparative Example 3 In this comparative example, aluminum current collectors were prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0092] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0093] (2) Place the pretreated aluminum foil in the electrolyte, start the asymmetric alternating current with a frequency of 220 Hz, a duty cycle of 1:3, and a forward current density of 20 mA / cm². 2 Reverse current density 8 mA / cm 2 The temperature was 40±2℃ and the time was 120 s.
[0094] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0095] Comparative Example 4 In this comparative example, aluminum current collectors were prepared according to the following method: 1. Pretreatment: The aluminum foil (20 μm thick) was cleaned with an alkaline solution (alkaline solution: 5 wt% NaOH aqueous solution, 40℃, 20s) to remove the surface oxide layer and surface oil.
[0096] 2. Alternating current corrosion: (1) Preparation of electrolyte: Mix concentrated hydrochloric acid (mass fraction 37%), concentrated sulfuric acid (mass fraction 98%), concentrated nitric acid (mass fraction 69%) and deionized water to obtain the electrolyte. The volume ratio of concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid and deionized water is 3:1:1:5.
[0097] (2) Place the pretreated aluminum foil in the electrolyte, start a symmetrical alternating current with a frequency of 100 Hz, a duty cycle of 1:1, and a current density of 20 mA / cm². 2 The temperature was 40±2℃ and the time was 120 s.
[0098] 3. Post-processing: The etched aluminum foil obtained in step 2 was rinsed with deionized water and dried with hot air at 60°C to obtain an aluminum current collector.
[0099] Test case The aluminum current collectors prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to the following tests: 1. Surface roughness: Measured using a white light interferometer (Bruker ContourGT) according to ISO 4287 standard; 2. Contact resistance: Tested using the four-probe method (Keithley 2450) at a constant current of 1 A; 3. Mechanical properties: Tested using a universal testing machine (Instron 5967) according to ASTM E8 standard, tensile rate 2 mm / min; 4. Process efficiency: Based on the processing time and energy consumption per batch (kW·h / m³) 2 Comprehensive calculation.
[0100] The results are shown in Table 1. The overall performance of the aluminum current collectors prepared in Examples 1-5 is better than that of Comparative Examples 1-4. While improving the surface roughness, they significantly reduce the specific contact resistance, while also having a high tensile strength retention rate and a short processing time.
[0101] Comparative Example 1 uses DC etching, which results in uneven distribution of surface pores, a significant decrease in mechanical properties, and low process efficiency.
[0102] Comparative Example 2 employed a traditional chemical etching process. Due to the lack of electric field-directed regulation, the corrosion process was dominated by the anisotropy of surface energy. The etching rate of the (100) crystal plane of the aluminum foil was three times faster than that of the (111) crystal plane, forming anisotropic corrosion pits. This non-uniform structure resulted in an effective contact area increase of only about 30%, leading to a specific contact resistance still as high as 28 mΩ·cm. 2 Meanwhile, prolonged immersion (240s) induces intergranular corrosion. Although the tensile strength retention rate reaches 92%, the process time is extended to 4 minutes, and energy consumption increases by 50%.
[0103] Comparative Example 3 uses a 220Hz high-frequency AC current. The excessively short cycle time (4.5ms) leads to insufficient ion migration, resulting in discrete pitting corrosion on the surface instead of a continuous honeycomb structure, which significantly degrades the mechanical properties.
[0104] Comparative Example 4 uses symmetrical alternating current (duty cycle 1:1), with a forward / reverse current density of 20 mA / cm². 2 This leads to a dynamic imbalance between corrosion and redeposition, causing the specific contact resistance to rise to 24 mΩ·cm. 2 The tensile strength retention rate was only 89.7%, demonstrating the crucial role of asymmetric current parameters in structural integrity.
[0105] Example 2, by increasing the frequency to 180 Hz, completes more "activation-passivation" cycles per unit time. Combined with a duty cycle of 1:4 to extend the reverse repair time, it accelerates ion migration under high-temperature conditions. This parameter combination results in a denser honeycomb structure on the aluminum foil surface (roughness 2.1 μm) while shortening the processing time to 1.5 minutes. The continuous repair effect of the reverse current maintains a 95.2% tensile strength retention rate, and the cavitation effect generated by the high-frequency pulse promotes electrolyte renewal, reducing the specific contact resistance to 15 mΩ·cm. 2 .
[0106] Example 3 uses a lower frequency of 80 Hz to extend the single-cycle treatment time, combined with a 1:2 duty cycle to enhance the forward corrosion advantage. At a lower temperature of 30°C, the activation and dissolution rate of aluminum decreases, and the passivation effect of nitric acid becomes more significant. Extending the treatment time to 150 s causes the corrosion to extend laterally, forming a honeycomb structure with larger but uniformly distributed pores (roughness 1.5 μm). Moderate repair with reverse current results in a tensile strength retention rate of 97.8%, while the shallower pore depth structure leads to a slightly higher specific contact resistance (20 mΩ·cm). 2 However, it is more suitable for applications that require high mechanical stability.
[0107] Example 4: Due to the absence of nitric acid in the electrolyte, the passivation effect was weakened, leading to a decrease in pore structure uniformity, surface roughness (1.6 μm), and specific contact resistance (22 mΩ·cm). 2 The performance was slightly inferior to that of the standard embodiment 1, but it still maintained a 96% tensile strength retention rate through periodic repair with asymmetric alternating current.
[0108] Example 5 uses an electrolyte combination of concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 45:3:20. Although the highest surface roughness (2.3 μm) was obtained, excessive corrosion caused the tensile strength retention rate to drop to 93.5%, which verifies that the electrolyte ratio should be controlled within the preferred range of (1-5):(1-3):(1-3).
[0109] Table 1 Performance Test of Aluminum Current Collector
[0110] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A method for preparing an aluminum current collector, characterized in that, include: The aluminum foil is pretreated to remove the oxide layer and contaminants from its surface. The pretreated aluminum foil is placed in an electrolyte for alternating current etching to obtain etched aluminum foil. The etched aluminum foil is then post-processed to obtain the aluminum current collector; The alternating current corrosion treatment uses asymmetric alternating current. The frequency of the asymmetric alternating current is 10 Hz to 200 Hz; The duty cycle of the asymmetric alternating current is 1:2 to 1:4; The forward current density of the asymmetric alternating current is 10 mA / cm². 2 ~30 mA / cm 2 ; The reverse current density of the asymmetric alternating current is 5 mA / cm². 2 ~10 mA / cm 2 ; The temperature for the AC corrosion treatment is 20℃~60℃; The time for the alternating current etching treatment is 10 s to 180 s; The electrolyte is obtained by mixing concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid with deionized water in a volume ratio of (1~5):(1~3):(1~3); wherein the volume of the deionized water is less than or equal to the sum of the volumes of the concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid; the mass fraction of the concentrated hydrochloric acid is ≥36%; the mass fraction of the concentrated sulfuric acid is ≥98%; and the mass fraction of the concentrated nitric acid is ≥69%. The duty cycle of the asymmetric alternating current refers to the time ratio of the forward current to the reverse current within a complete current cycle.
2. The method according to claim 1, characterized in that, The pretreatment includes cleaning the aluminum foil with an alkaline solution.
3. The method according to claim 2, characterized in that, The alkaline solution includes a sodium hydroxide solution, wherein the sodium hydroxide solution contains 2 to 8 wt% sodium hydroxide.
4. The method according to claim 2, characterized in that, The alkaline cleaning solution is applied at a temperature of 30℃~50℃ for 10 s~30 s.
5. The method according to claim 1, characterized in that, The post-processing includes washing and drying.
6. The method according to claim 5, characterized in that, The drying temperature is 50℃~70℃.
7. An aluminum current collector, characterized in that, The aluminum current collector is prepared by the method described in any one of claims 1 to 6.
8. The aluminum current collector according to claim 7, characterized in that, The surface of the aluminum current collector has a honeycomb structure.
9. The aluminum current collector according to claim 7, characterized in that, The surface roughness of the aluminum current collector is not less than 1.5 μm.
10. The aluminum current collector according to claim 7, characterized in that, The specific contact resistance of the aluminum current collector is 15 mΩ·cm. 2 ~20 mΩ·cm 2 .
11. The aluminum current collector according to claim 7, characterized in that, The tensile strength retention rate of the aluminum current collector is not less than 95%.
12. A secondary battery, characterized in that, include: The aluminum current collector according to any one of claims 7-11.
13. An electrical appliance, characterized in that, include: The secondary battery of claim 12.
Citation Information
Patent Citations
Multi-stage frequency-conversion eroding method for anode foil of aluminium electrolytic capacitor
CN101225539A
Method for preparing formed foil by using asymmetric intermittent positive and negative combined pulses
CN112530708A